Ponctuation et mise en page dans Madame Bovary : les interventions de Flaubert sur le manuscrit du copiste - Stella Mangiapane (Flaubert: Revue Critique et Génétique)
This paper deals with the last stages of Madame Bovary’s genesis, which are attested, in the final manuscript, by the corrections made by Flaubert himself on his own work and on the deliberate or accidental modifications made by the copyist, with regard to punctuation or layout. Two specific aspects of Flaubert’s writing will be analysed: first, the rhythmic more than logical function that Flaubert attributed to punctuation and second, the constant attention paid to the creation of a particular rhythm of the page. The latter derives from both the visual and narrative elements and is linked to the concatenation of paragraphs, considered as narrative strategic units. This paper thus investigates the last stage of the writer’s work, comparing, on the one hand, the final autographed manuscript and, on the other hand, both the edition of the novel published on the Revue de Paris (October-December 1856) and the first printed edition (Michel Lévy frères, 1857). These different comparisons will highlight the scope and range of the questions raised by Flaubert’s use of punctuation.